Picture of Society Stigma Towards People with Mental Disorders (ODGJ) - Riani Pradara Jati; Muhammad Arief Nurfaizin; Rina Anggraeni (Global Health Science Group, 2025)
Mental disorders are caused by the instability of individual psychosocial functions, although some are related to the dysfunction of certain physical or neurological organs. Mental health is more difficult to observe and so often does not get enough attention from the public. Objective: to find out the community's stigma against ODGJ in Krompaan Village, Gemuh District. This study used a descriptive survey study design, a sample of 400 samples, the sampling technique used was purposive sampling. The questionnaire used is the community's stigma against ODGJ from 16 questions. Statistical analysis using univariate analysis. The stigma of the labeling community is mostly sufficient as much as 348 (87.0%), the stigma of the stereotyping community is sufficient as much as 335 (83.8%), the stigma of the separation community is sufficient as much as 171 (42.8%), the community stigma on the aspect of discrimination is sufficient, namely as many as 201 (50.3%), this is because there are some people who demean, do not consider and harass ODGJ patients.